Crisis? What crisis? Cross-cultural psychology's appropriation of cultural psychology. (September 2015) - Ellis, Basia D; Stam, Henderikus J
Whereas cross-cultural psychology and cultural psychology have been distinguished as separate projects for decades, talk about their possible collaboration is becoming increasingly common. Several scholars have described their differences as essentially non-oppositional and the latest Handbook of Cultural Psychology combines articles from both research traditions. This paper scrutinizes these consolidating efforts first by tracing historically how the two accounts of culture (cultural and cross-cultural) developed, and second, by examining whether their long-standing epistemological premises allow for the kind of collaboration advocated by some scholars. We argue that attempts to combine the disciplines come primarily from cross-cultural psychologists who appear increasingly challenged by cultural and indigenous psychological approaches. Attempts at a merger have been twofold: on the one hand, cross-cultural psychologists who seek to preserve the status of their discipline have expanded its scope to include cultural theorists; on the other hand, cross-cultural scholars persuaded by cultural theories are creating a new blend of 'experimental cultural psychology' that seeks to accommodate both programs. These proposals, in our view, exemplify a cross-cultural discipline in crisis, struggling to account for a growing cultural psychology. We conclude that the overlapping interests between cross-cultural and cultural scholars make this a propitious time for cross-disciplinary dialogue.